The Effect of Discipline, Work Commitment, and Work Motivation on Employee Job Satisfaction - Hartati; Mulyana Machmud; Hasanuddin (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Job satisfaction is essential for achieving organizational objectives, with work discipline, work commitment, and work motivation identified as key factors shaping employee attitudes and performance. The purpose of this study is to analyze the influence of work discipline, work commitment, and work motivation on employee job satisfaction. The research method uses a descriptive quantitative approach, involving 33 employees selected through a saturated sampling technique. Data were obtained using a 1–5 Likert-scale questionnaire and analyzed through multiple linear regression with SPSS version 25. The findings show that work discipline, work commitment, and work motivation each have a positive and significant effect on employee job satisfaction. Work motivation emerges as the most dominant variable, indicated by the highest regression coefficient. The simultaneous test confirms that all three variables collectively influence job satisfaction. The coefficient of determination (R² = 0.878) reveals that 87.8% of the variation in job satisfaction is explained by the studied variables, while 12.2% is affected by other factors not included in the model. These results emphasize the strategic importance of strengthening discipline, enhancing commitment, and improving motivation to elevate employee satisfaction and organizational performance.